Regeneration and In Vitro Flowering in Brassica Campestris (L.) Var. Bhavani - Verma, Rinki; Singh, RR (Our Nature, 2008)
Multiple shoot formation and in vitro flowering was found in Brassica campestris (L.) var. Bhavani. Maximum numbers of shoots were produced in both cotyledonary node and shoot apex explants on MS-media supplemented with BA (2.5 mg/l) + IAA (1.0 mg/l) + Kn (0.5 mg/l). Maximum flowering (50%) was noted at IBA (1.5 mg/l) + IAA (1.0 mg/l) + Kn (0.5 mg/l) in the shoots from cotyledonary nodes. In vitro flowering may contribute in many ways to Brassica Improvement Programs. The shoots rooted well in the half and full strength media each with IBA (1.0 mg/l) and NAA (1.0 mg/l) and the plantlets have been maintained. Keywords: Brassica campestris, In vitro flowering, Regeneration. doi:10.3126/on.v5i1.793 Our Nature (2007)5:21-24